Progress in the application of molecular imaging technology in immunological tolerance and immune metabolism visualization research - Li, Kailang; Xie, Fang; Xiong, Yongfu; Jiang, Jin; Huang, Bifan (Frontiers in Immunology, 2025)
Immunological tolerance and immune metabolism play crucial roles in maintaining immune homeostasis and the immune response to diseases. The advancement of molecular imaging technologies, particularly optical molecular imaging, nuclear medicine imaging, and magnetic resonance imaging, has led to a significant progress in the visualization of immune tolerance and immune metabolism. Molecular imaging technologies enable real-time monitoring and analysis of dynamic changes in immune tolerance mechanisms and immune metabolism in living organisms, allowing the development of new strategies for early disease diagnosis, targeted therapy, and immunotherapy. This article reviews the latest advancements in the application of molecular imaging technologies in the fields of immunological tolerance and immune metabolism, with a focus on their applications in the regulation of immune tolerance regulation, immune metabolism, and immunotherapy.